People Skills: How to Assert Yourself, Listen to Others, and Resolve ConflictsBolton Robert. People Skills: How to Assert Yourself, Listen to Others, and Resolve Conflicts. Englewood Cliffs, N.J.: Prentice-Hall, 1979, 300 pp., $4.95 paperback. - Hammer, Mark (Academy of Management Review, 1980)
The article reviews the book ?People Skills: How to Assert Yourself, Listen to Others, and Resolve Conflicts,? by Robert Bolton.